2006
DOI: 10.1177/153537020623100804
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Adhesion of T Lymphocytes to Endothelial Cells Revealed by Atomic Force Microscopy

Abstract: The recruitment of T lymphocytes to lymphoid organs or sites of inflammation is a crucial step in adaptive immunity. These processes require endothelial activation and expression of adhesion molecules, including E- and P-selectins, intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1). However, the complete characterization of the adhesion strength and dynamics between lymphocytes and endothelial cells has been hampered by the lack of sensitive quantitative techniques. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 30 publications
7
56
0
Order By: Relevance
“…Benoit and coworkers pioneered the field of AFM based cell-cell adhesion measurements with Dictyostelium discoideum cells and found force values in the low nN regime for short contact times (11). In another study, Moy and coworkers examined interaction forces between human umbilical vein endothelial cells (HUVECs) and Jurkat T cells over a period of 10 s, yielding values in the range of 100 pN (13). Thus, so far, the majority of adhesion-related SCFS studies performed by AFM concentrated on short-time effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benoit and coworkers pioneered the field of AFM based cell-cell adhesion measurements with Dictyostelium discoideum cells and found force values in the low nN regime for short contact times (11). In another study, Moy and coworkers examined interaction forces between human umbilical vein endothelial cells (HUVECs) and Jurkat T cells over a period of 10 s, yielding values in the range of 100 pN (13). Thus, so far, the majority of adhesion-related SCFS studies performed by AFM concentrated on short-time effects.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-cell adhesion has been studied by micropipette aspiration techniques (9, 10) and atomic force microscopy (AFM) (11)(12)(13). The recent years have seen a significant increase of AFM-related studies in biological systems, and single-cell force spectroscopy (SCFS) by AFM has been established as an important tool for the study of cell adhesion (14).…”
Section: Immune Synapse Formation Determines Interaction Forces Betwementioning
confidence: 99%
“…Most AFM approaches have focused on isolated receptor ligand interactions either using purified molecules or cells interacting with immobilized purified ligands (23,24). Other SCFS experiments have only concentrated on short-time effects, such as a 10-s contact between endothelial cells and Jurkat T cells (25). In this study, interaction forces of only 100 pN were reported.…”
Section: Discussionmentioning
confidence: 84%
“…Concanavalin A (ConA) functionalization of cantilevers was performed as described previously (Zhang et al, 2006). In brief, tipless Arrow TL1 cantilevers (Nanoworld, NeuchĂątel, Switzerland) with a nominal spring constant of 0.03 N/m were used.…”
Section: Single-cell Force Spectroscopymentioning
confidence: 99%